2015
DOI: 10.1007/s12686-015-0475-x
|View full text |Cite
|
Sign up to set email alerts
|

Species identification and molecular sexing from feces of Kashmir stag (Cervus elaphus hanglu)

Abstract: We developed an easy and efficient molecular genetics technique where species identification and sexing of Kashmir stag (Cervus elaphus hanglu) was carried out simultaneously in a single PCR. The technique has assigned the sexes of known and unknown individuals without any ambiguity and has proven its applicability in identifying sexes of several other cervids including chital, sambar and hog deer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Another encouraging result from this study that has significant swamp deer conservation implications is the moderate heterozygosity and low inbreeding status of this population. The heterozygosity value ranged between 0.38 to 0.84 across loci (Average Ho= 0.51, SD=0.10) and is consistent with other deer species (Kuehn et al 2003;Feulner et al 2004;Lee et al 2015;Mukesh et al 2015), including previous studies on swamp deer (Kumar et al 2017). However, the low inbreeding value (FIS) contradicts earlier reports from JJCR (Kumar et al 2017) which forms only a part of the entire Ganges population.…”
Section: Discussionsupporting
confidence: 84%
“…Another encouraging result from this study that has significant swamp deer conservation implications is the moderate heterozygosity and low inbreeding status of this population. The heterozygosity value ranged between 0.38 to 0.84 across loci (Average Ho= 0.51, SD=0.10) and is consistent with other deer species (Kuehn et al 2003;Feulner et al 2004;Lee et al 2015;Mukesh et al 2015), including previous studies on swamp deer (Kumar et al 2017). However, the low inbreeding value (FIS) contradicts earlier reports from JJCR (Kumar et al 2017) which forms only a part of the entire Ganges population.…”
Section: Discussionsupporting
confidence: 84%
“…Studying bear movement patterns using traditional field techniques is difficult due to their crepuscular/nocturnal behavior, large home range sizes and their use of steep and rugged terrain. Therefore, molecular markers and non-invasive genetic sampling have been used in several studies to study the various important aspects of ecology and genetics of free ranging animals including gene flow [ 17 ], population genetic structure [ 18 , 19 ], population demography [ 20 ], genetic diversity [ 21 , 22 ], sex identification [ 23 , 24 ], individual identification [ 18 , 25 ] and evolutionary history [ 22 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, live animals are relatively easily sexed. Previous studies have demonstrated the ability to sex red deer and other ruminants by applying polymerase chain reaction (PCR) techniques to organic samples, such as feces and bones (Huber et al, 2002; Jafar & Flint, 1995; Pajares et al, 2007; Pfeiffer & Brenig, 2005; Sharma et al, 2015; Zenke et al, 2022). DNA testing can be expensive, time‐consuming, and prone to failure in the context of zooarchaeology, depending on the number of specimens found at a given site and their state of preservation.…”
Section: Introductionmentioning
confidence: 99%